Separation of three isoenzymes of N-acetyl-β-D-hexosaminidase from human tissues by cellulose acetate membrane electrophoresis. Issue 11 (November 1974) - Westwood, A.; Raine, D. N.
Abstract : The separation of N-acetyl-β-D-hexosaminidase isoenzymes from human tissues is used in the diagnosis and differential diagnosis of GM2 gangliosidosis, since in type 1 the A isoenzyme is deficient and in type 2 both the A and B isoenzymes are deficient. Peripheral blood leucocytes are commonly used for these investigations, and the present study demonstrates that, in addition to these two isoenzymes, a third isoenzyme can be separated from leucocytes by cellulose acetate membrane electrophoresis. This isoenzyme is more anodic than the A and B isoenzymes and is similar to the hexosaminidase C isoenzyme recently reported in embryonic tissue extracts. The isoenzyme was also clearly demonstrable in human liver and kidney but was present in much lower concentrations in cultured cells. It could be demonstrated in leucocytes even after prolonged storage at −20°, and, like the A isoenzyme, is partially inactivated by a short exposure to heat.